PENINGKATAN HASIL BELAJAR SISWA MATERI PERBEDAAN BUDAYA DAN AGAMA MELALUI MEDIA POP UP BOOK - Dwi Firmansyah, Rizki; Agus Wardhono; Badri Atul Fikriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the learning outcomes of sixth-grade students at SDN Sidomulyo 2 Tuban on the subject of cultural and religious differences through the use of pop-up books. The research method used was Classroom Action Research (CAR) with two cycles. The results of the study indicate a significant improvement in learning outcomes from Cycle I to Cycle II, both in terms of grades and student and teacher activities. The pop-up book medium has proven to make learning more engaging and effective.